2013
DOI: 10.1177/0958928712456575
|View full text |Cite
|
Sign up to set email alerts
|

Social workers’ perceptions of the causes of poverty in the Nordic countries

Abstract: Street-level bureaucrats have been given an increasing role in the implementation of policies aimed at the poor. The article analyses: (1) how social workers in the Nordic countries explain the causes of poverty and whether there are variations between countries in social workers’ perceptions; and (2) the nature of the impact, if any, of various individual- and municipal-level factors on social workers’ perceptions of the causes of poverty. Survey data gathered from social workers in four countries are analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(73 citation statements)
references
References 39 publications
3
65
1
4
Order By: Relevance
“…Furthermore, it seems that there is not a specific Nordic way of perceiving privatization of social work services because the variation between these countries is relatively large (see also Blomberg et al, 2013;. Support for for-profit organizations was strongest in Italy, closely followed by Finland and Denmark.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, it seems that there is not a specific Nordic way of perceiving privatization of social work services because the variation between these countries is relatively large (see also Blomberg et al, 2013;. Support for for-profit organizations was strongest in Italy, closely followed by Finland and Denmark.…”
Section: Resultsmentioning
confidence: 94%
“…Previous research has shown major similarities in the attitudes of Nordic social workers concerning professional and social welfare issues (Blomberg, Kallio, Kroll, & Erola, 2013;Meeuwisse, Scaramuzzino, & Swa¨rd, 2011). This article compares the attitudes towards privatization among social workers in four Nordic countries -Denmark, Finland, Norway, and Sweden -and in Italy.…”
Section: Aim and Research Questionsmentioning
confidence: 97%
“…Global neoliberal policies have been resisted by many countries, such as Finland, because comprehensive public welfare services were considered as an investment. However, during the past few decades, the attitude to European public welfare measures shifted towards being considered basically as a “burden”, and they experienced the effects of privatisation with an increasing dominance of ideas of competitiveness and productivity (Blomberg et al , 2013). In addition, the solidarity between EU states has been fragmented, and there is no solidarity towards people seeking protection.…”
Section: Globalisation Nation States and Migrationmentioning
confidence: 99%
“…In the same time, countries such as the United States of America, Italy, Austria, Spain, Canada and Portugal stand towards an individualistic causal attribution of poverty, on a societal level. Research of [1] identified a rather structuralist attribution of poverty in the Nordic countries, while [14] showed that Finland manifests a different approach towards poverty causality, considering that the individualistic and fatalist causes should be viewed as the most important. Costa and Dias, in their paper [3], have an exhaustive presentation of all these research results and also others that we didn't mention here.…”
Section: Problem Statementmentioning
confidence: 99%
“…We can mention here the following sources: [1], [3], [9], [10], [11], [12], [13], [16]. The research of [16] identified three groups of countries according to the identified tendency on a societal level to causally attribute poverty.…”
Section: Problem Statementmentioning
confidence: 99%